Fire Forest and Land Control by Community in Pematang Rahim Village, Jambi Province - Saharjo, Bambang Hero; Zulkarnain, Muhammad Rafi Putra (Journal of Tropical Silviculture, 2024)
Peatlands are lands rich in organic carbon. Therefore, dried peat soil becomes fuel when ignited. This research aims to identify and describe the causes, efforts to control forest and land fires, and land utilization by the community in Pematang Rahim Village, Jambi Province. This research uses a qualitative approach with methods of data collection through interviews, observations, and archival studies. Respondent selection is done using snowball sampling method. Data analysis is carried out descriptively qualitatively. The results indicate that the causes of land fires in Pematang Rahim Village are due to land clearing and human negligence. Fire mitigation efforts include patrols, socialization, the establishment of the Masyarakat Peduli Api (MPA), and the creation of fire prohibition sign. Fire suppression is carried out directly using fire extinguishing tools and helicopters. Land utilization in Pematang Rahim Village includes oil palm plantations, betel nut gardens, beekeeping, and swiftlet farming. Keywords: land fire, land utilization, MPA, peat